2021
DOI: 10.1108/itp-05-2021-0397
|View full text |Cite
|
Sign up to set email alerts
|

Examining digital information literacy as a determinant of women's online shopping behavior

Abstract: PurposeThe present study aims to examine the current digital information literacy (DIL) skills of female online shoppers in Lahore city of Pakistan. Data were gathered from a purposive sampling of women, aged between 20–50 years who were buying products online, not from the traditional retail stores. Out of 309 received questionnaires, 269 responses were useable and were utilized for data analysis. Descriptive and inferential statistics were used to deduce inferences.Design/methodology/approachQuantitative res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
3
10
0
Order By: Relevance
“…PIM involves methods and practices to store, retrieve and organize information in an effective manner (Al Nasar et al , 2011). Literature validated that individuals need to be trained in IL and information management (Ince et al , 2019; Mahmood et al , 2021; Safdar and Idrees, 2020; Safdar and Idrees, 2021). Increasing digital engagements exponentially caused a rise in personal information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…PIM involves methods and practices to store, retrieve and organize information in an effective manner (Al Nasar et al , 2011). Literature validated that individuals need to be trained in IL and information management (Ince et al , 2019; Mahmood et al , 2021; Safdar and Idrees, 2020; Safdar and Idrees, 2021). Increasing digital engagements exponentially caused a rise in personal information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, these worries affect women more. Mahmood et al (2022), investigated the contemporary digital information literacy (DIL) competencies possessed by female individuals engaged in online shopping activities and indicated a significant relationship between digital information literacy skills and the online shopping behavior of women. Additional research findings suggested that the female participants exhibited a notable reluctance to partake in online shopping activities and hesitated to use credit/debit cards.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…However, these worries affect women more. Mahmood et al . (2022), investigated the contemporary digital information literacy (DIL) competencies possessed by female individuals engaged in online shopping activities and indicated a significant relationship between digital information literacy skills and the online shopping behavior of women.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…The level of digital literacy was related to age, education level, and Internet experience (e.g., years of use) (Hatlevik et al, 2018; Lee & Tak, 2022). In addition, the existing studies have investigated the effects of digital literacy on individual behavior, such as online privacy behavior (Park, 2011), online shopping behavior (Mahmood et al, 2021), and information use behavior (Noh, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%